Body design of electric three-wheeler - Romell , Joakim (My University, 2026)
Electric three-wheeler manufacturer Omotion, located in Lund, Sweden, was in the process of improving the performance of their only existing vehicle model, the Omotion 2. A new vehicle model was desired in which the performance increase could be implemented. Omotion wanted to achieve a “modern” and “sporty” design which utilised the performance efficiently. Aerodynamics was therefore a concern. Included in the requirements was that the design had to have a roof over the occupants. As a roof was a necessity, how individuals enter and exit the vehicle was considered in the work. Because the work was very aesthetics driven, aesthetic trends for motorcycles and sportscars in several Western European countries were studied. Naked and adventure motorcycles were determined to be trending and consisted of features such as exposed mechanics and small complex bodywork panels. Sports cars shared similarities such as low to the ground and slightly sloped hood. A function analysis was also done as part of the prestudy and guided the concept development. The function identified were kept vague to allow for a wide variety of solutions. Concept development was done with the help of sketches, morphological matrices, CAD models, and a clay model. Concept generation was also attempted using artificial intelligence (AI) but was unsuccessful. The work resulted in a satisfactory concept despite difficulties ascertaining the aerodynamic performance. Mechanical solutions to make the concept feasible would still be developed but the mechanisms were already in use on other vehicles. With continued development of the concept, Omotion should have the ability to realise the concept within ten years